Opini Audit Going Concern: Financial Distress, Kepemilikan Manajerial, Audit Tenure, Opinion Shopping, dan Solvabilitas - Sherly Amartasari; Eny Kusumawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The auditor issues a going concern audit opinion to ascertain whether the company is able to maintain its business continuity or not. Going concern audit opinion can be used as an early warning for users of financial statements to avoid errors in decision making. This study aims to analyze the effect of financial distress, managerial ownership, audit tenure, opinion shopping, and solvency on going concern audit opinion. Researchers conducted an empirical study on basic materials sector companies listed on the IDX for the 2021-2023 period. The sampling technique used purpose sampling. Based on the sampling criteria, 117 units of data were obtained. Researchers use logistic regression analysis tools and have passed the model suitability test, model feasibility test, and coefficient of determination test.. The results of the study provide empirical evidence that audit tenure, opinion shopping, and solvency affect going concern audit opinion. Meanwhile, financial distress and managerial ownership have no effect on going concern audit opinion. With the going concern audit opinion, it is a consideration for stakeholders in decision making.